Pendampingan Pengelolaan Pemasaran Online Kerupuk Bandeng di Kelurahan Sawah Luhur Kecamatan Kasemen Kota Serang - Wahyuddin; Deviyantoro; Darpi; Sawitri Nurhayati (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
Sawah Luhur Village is one of the villages in Kasemen District, Serang City, Banten Province. Communities in Sawah Luhur Village have quite diverse livelihoods to meet their needs, including fisheries, coffee shop businesses, buying and selling basic necessities or grocery stores, livestock businesses, artisans of processed milkfish crackers, carpentry, agriculture, and others. The marketing and sales process carried out by the processed food craftsmen is carried out only by opening stalls around the house and offering them to consumers who stop by at the stalls. The service team provides an understanding of bookkeeping administration, marketing and sales diversification by utilizing information technology. The method used is directly to the service location with the stages of situation analysis and identification of problems experienced by the craftsmen, discussions with the craftsmen and the preparation of mentoring activity plans and implementation of activities. This activity can increase partners' understanding of the formulation and benefits of bookkeeping administration and the use of information technology in marketing activities.